Business Analysis In Publishing Media: Internship at Outlook Publishing - Deva, Deepkumar (ATLAS SkillTech University, 2025)
This internship report: Exploring Business Analysis — My Internship at Outlook Publishing is a comprehensive reflection of how the journey was for me as an intern in that organization and having to work with business analysts. This post ensues on learning and practical knowledge gained by me during an internship program, as course curriculum in my second-year MBA at Atlas SkillTech University. I contributed in different aspects of business analysis, including data assembling and market research to sales trend understanding down the road strategic insights. I was advised by my academic faculty member Dr. Shashikant Deepak to understand the concepts of data-driven decision making through a series of structured cases that linked theoretical input to practical modules in real estate practice thereby mentoring me throughout the process.
Project Report on Business Analysis In Publishing Media: Internship at Outlook Publishing (2023-2025) Under the Guidance of Prof. Shashikant Patil
Keywords: Business Analysis; strategic insights; business analysts